2016
DOI: 10.1091/mbc.e16-01-0041
|View full text |Cite
|
Sign up to set email alerts
|

The RhoE/ROCK/ARHGAP25 signaling pathway controls cell invasion by inhibition of Rac activity

Abstract: New molecular pathways involved in alveolar rhabdomyosarcoma aggressiveness are found by identifying the RhoE/ROCK/ARHGAP25 signaling pathway as promoting the invasive potential of alveolar rhabdomyosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 39 publications
1
31
1
Order By: Relevance
“…Additionally, ARHGAP25, which inhibits Rac activity, is upregulated in FPRMS and its knockdown inhibits invasion. Thus, ROCK acts in FPRMS by upregulating ARHGAP25 and subsequently inhibiting Rac function, which subsequently promotes motility and cellular invasion [84].…”
Section: G Protein and G Protein-coupled Receptorsmentioning
confidence: 99%
“…Additionally, ARHGAP25, which inhibits Rac activity, is upregulated in FPRMS and its knockdown inhibits invasion. Thus, ROCK acts in FPRMS by upregulating ARHGAP25 and subsequently inhibiting Rac function, which subsequently promotes motility and cellular invasion [84].…”
Section: G Protein and G Protein-coupled Receptorsmentioning
confidence: 99%
“…We identified 1194 genes enriched in ARMS biopsies; 40% of which were in the vicinity of previously identified PAX3FOXO1 bound cis-regulatory modules (CRM) [11,12] (Fig 2B). This list of genes largely comprised previously identified PAX3FOXO1 dependent ARMS markers, such as ALK, ARHGAP25, or FGFR4 [9,47]. Functional annotation of these genes indicated that they encode for developmental regulators of many embryonic lineages known to be dependent on PAX3 and PAX7 activities ( Fig 2C, Table S2) [48], and not exclusively of the muscle lineage.…”
Section: Paxfoxo1 Tfs Convert Chick Neural Cells Into Arms Like-cellsmentioning
confidence: 96%
“…Further analysis has revealed that miR-17 directly represses the cell cycle regulator and RB-family member P130 (RB transcriptional co-repressor like 2, RBL2 ), a tumor suppressor that also negatively regulates β-catenin levels and Wnt signaling ( Ma et al, 2012 ). MiR-17 also targets and inhibits PTEN ( Fang et al, 2014 ) and RHOE ( RND3 ), which encodes a GTP-binding protein (without GTPase activity) that is reduced in CRC and can repress tumor cell invasion ( Thuault et al, 2016 ), promote contact inhibition ( Hernández-Sánchez et al, 2015 ) and downregulate Notch signaling ( Tang et al, 2014b ; Zhu et al, 2014b ).…”
Section: The Mir-17 Oncomir Family and Modulation Of Tgf-β Signalingmentioning
confidence: 99%